PENGEMBANGAN MODUL PEMBELAJARAN PAI BERBASIS SAINTIFIK PADA MATERI PUASA RAMADHAN KELAS 5 DI SD N 06 LADANG PADI KABUPATEN SOLOK - Indah Melia Kembang; Fajriyani Arsya (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is based on the fact that at SD N 06 Ladang Padi, Solok Regency, there are limited PAI textbooks in schools, there are no additional learning resources for students in the form of modules, learning media is still lacking in support in the classroom in the form of electronic media, and learning facilities and infrastructure are still minimal. Student learning resources are only limited to teacher explanations. The aim of this research is to produce a scientifically based PAI learning module, especially on Ramadan fasting material. The type of research is development (Reseach and Development) which is abbreviated as R&D which was developed by Thiagadjaran of the 4D type (Define, Design, Develov, Disseminate). The results of the research show that scientific-based PAI learning modules can be used by teachers and students in the Ramadan fasting material after product testing by carrying out validation tests by several experts, practicality by PAI teachers, and effectiveness by grade 5 students with validation results of 0.79, practicality test of 0 .85, and an effectiveness test of 0.67. From these results, the development of scientifically based PAI learning modules is suitable for use in PAI learning